Influence of Ag on the precipitates in Mg-8Gd-0.8Y-0.5Zn-0.3Zr alloy - Cheng Renju; Zhou Yongfeng; Wang Haijun; Jiang Linxi; Tang Aitao; Jiang Bin (Journal of Materials Research and Technology, 2025)
This paper investigates the influence of Ag element on the microstructure and mechanical properties, as well as the synergistic strengthening and toughening mechanisms of the Mg-8Gd-0.8Y-0.5Zn-0.3Zr alloy. The study shows that the addition of 0.1 wt% Ag increases the yield strength, ultimate tensile strength, and elongation to 225 MPa, 338 MPa, and 16.5%, respectively, which are 25%, 14%, and 73% higher compared to the Ag-free alloy. The introduction of Ag increases the aspect ratio of nanoscale precipitates β′ phases from 4.4:1 to 6:1, enhancing the ability of dislocation pinning and thereby improving the alloy's strength. Moreover, Ag addition can reduce the volume fraction of 18R-LPSO phases, increases the numbers of I1 (ABCB) and I2 (ABCA) stacking faults, and particularly enhancing the activation of <c+a> slip systems, thus promoting the alloy's ductility.